Domain wall as regular solutions in GR with two phantom scalar fields - Urazalina, A.; Dzhunushaliev, V. (Recent Contributions to Physics, 2016)
Domain solutions in general relativity created with two phantom scalar fields are investigated. It has been shown that the solutions with finite energy exist for some specific values of the parameters m1, m2 only. Corresponding field equations are solved numerically as nonlinear eigenvalue problem where the parameters m1, m2 are eigenvalues and scalar fields are eigenfunctions. The family of solutions depending on values of scalar fields at the center of domain mouth is obtained. The dependence of parameters m1, m2on initial values c0 is investigated.